Absorbing aerosol decreases cloud cover in cloud‐resolving simulations over Germany. (7th October 2021) - Senf, F.; Quaas, J.; Tegen, I.
Abstract: Aerosol can affect clouds in various ways. Beside the microphysical impact of aerosol particles on cloud formation, the interference of aerosol with atmospheric radiation leads to changes in local heating, surface fluxes and thus mesoscale circulations, all of which may also modify clouds. Rather little is known about these so‐called semi‐direct effects in realistic settings – a reason why this study investigates the impact of absorbing aerosol particles on cloud and radiation fields over Germany. Using advanced high‐resolution simulations with grid spacings of 312 and 625 m, numerical experiments with different aerosol optical properties are contrasted using purely scattering aerosol as a control case and realistic absorbing aerosol as a perturbation. The combined effect of surface dimming and atmospheric heating induces positive temperature and negative moisture anomalies between 800 and 900 hPa, impacting low‐level cloud formation. Decreased relative humidity as well as increased atmospheric stability below clouds lead to a reduction of low‐level cloud cover, liquid water path and precipitation. It is further found that direct and semi‐direct effects of absorbing aerosol forcing have similar magnitudes and contribute equally to a reduction of net radiation at the top of the atmosphere. Abstract : Atmospheric aerosol particles can absorb solar radiation, altering the thermal structure of the atmosphere and surface fluxes. Using advanced high‐resolution simulations over Germany with grid spacings of 312 and 625 m, we find that boundary‐layer absorbing aerosol reduces low‐level cloud cover, liquid water path and precipitation. Direct and semi‐direct effects have similar magnitudes and contribute equally to a positive absorbing aerosol forcing.